2010
DOI: 10.1186/1746-4269-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicine of the Kagera Region, north western Tanzania. Part 2: The medicinal plants used in Katoro Ward, Bukoba District

Abstract: BackgroundThe Kagera region of north western Tanzania has a rich culture of traditional medicine use and practices. The dynamic inter-ethnic interactions of different people from the surrounding countries constitute a rich reservoir of herbal based healing practices. This study, the second on an ongoing series, reports on the medicinal plant species used in Katoro ward, Bukoba District, and tries to use the literature to establish proof of the therapeutic claims.MethodologyEthnomedical information was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 29 publications
12
28
0
2
Order By: Relevance
“…3). This result is in agreement with similar studies carried out in the Morogoro region [18] and other areas of Tanzania, where Leguminosae, Compositae and Solanaceae were among the most aboundant families [13, 16, 18]. In comparison with previous studies [13, 16, 18], the present data revealed a large presence of Lamiaceae, probably due to the widespread coltivation of this plant family (e.g., Ocimum tenuiflorum L., O. gratissimum L.) around the villages.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…3). This result is in agreement with similar studies carried out in the Morogoro region [18] and other areas of Tanzania, where Leguminosae, Compositae and Solanaceae were among the most aboundant families [13, 16, 18]. In comparison with previous studies [13, 16, 18], the present data revealed a large presence of Lamiaceae, probably due to the widespread coltivation of this plant family (e.g., Ocimum tenuiflorum L., O. gratissimum L.) around the villages.…”
Section: Resultssupporting
confidence: 93%
“…This result is in agreement with similar studies carried out in the Morogoro region [18] and other areas of Tanzania, where Leguminosae, Compositae and Solanaceae were among the most aboundant families [13, 16, 18]. In comparison with previous studies [13, 16, 18], the present data revealed a large presence of Lamiaceae, probably due to the widespread coltivation of this plant family (e.g., Ocimum tenuiflorum L., O. gratissimum L.) around the villages. Data evidenced the absence of plants belonging to the Rubiaceae family, as instead previously detected in other studies in the Morogoro region [18]; this was most probably due to the lack of forest areas nearby the studied villages and to the fact that most plants were collected in grassland and shrub areas, where this family is rarely present.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations